Efek Pemberian Kandungan Isoflavon pada Kedelai dalam Menurunkan Berat Badan - Syinthia Wulan Perdana (Jurnal Medika Hutama, 2021)
Obesity is an excessive accumulation of fat due to an imbalance of energy intake (energy intake) with energy used (energy expenditure) for a long time. Overweight and obesity are the biggest risk causes of global death. The occurrence of this disease is associated with changes in diet and daily activities. The method used by the author is a literature review study from several national and international journals. This method is used with the aim of presenting, increasing knowledge and understanding of this article by summarizing research material on a specific topic focus. From several studies conducted, it was found that consumption of soybeans containing isoflavones had a significant relationship with the incidence of weight loss.